2019
DOI: 10.1016/j.bbr.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of acute high-intensity exercise on electrophysiological indices of attention processes in young adult men

Abstract: HighlightsHigh-intensity exercise improved brain measures of attention processes.Fitness and physical activity level were not related to degree of improvement.We found no effects of exercise on subsequent Flanker and Reaction-time tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…In studies examining the effects of acute aerobic exercise, similar results as in the current study were found, i.e. no effects on response preparation, reflected by no alterations in CNV amplitude after either cycling (Du Rietz et al, 2019;Stroth et al, 2009) or running (Tsai et al, 2014). In those studies the exerting intervention was also not task-specific for the task used to assess the CNV.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In studies examining the effects of acute aerobic exercise, similar results as in the current study were found, i.e. no effects on response preparation, reflected by no alterations in CNV amplitude after either cycling (Du Rietz et al, 2019;Stroth et al, 2009) or running (Tsai et al, 2014). In those studies the exerting intervention was also not task-specific for the task used to assess the CNV.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding PE, acute aerobic exertion was shown not to affect late CNV (Du Rietz et al, 2019;Stroth et al, 2009;Tsai et al, 2014). The influence of isometric trunk muscle exertion on late CNV was not yet studied.…”
Section: Introductionmentioning
confidence: 96%
“…In total 71 papers were eligible for this review and meta-analysis. Overall, 44 studies (Aguirre-Loaiza et al, 2019;Akatsuka et al, 2015;Basso et al, 2015;Benzing et al, 2016;Browne et al, 2016;Budde et al, 2010Budde et al, , 2008Chang & Etnier, 2009;Chang et al, 2011;Coles & Tomporowski, 2008;Cooper et al, 2016Cooper et al, , 2012ÉW et al, 2011;Guzmán & López-García, 2016;Hwang et al, 2016;Hwang & Lu, 2018;Jaffery et al, 2018;Lambourne, 2012;Lambourne et al, 2010;Mezcua-Hidalgo et al, 2019;Moore et al, 2012;Murray & Russoniello, 2012;Palmiere et al, 2018;Peruyero et al, 2017;Pontifex et al, 2009;Prashanth, 2020;Du Rietz et al, 2019;Schwarck et al, 2019;Sipavičienė et al, 2012;Sperlich et al, 2018;Takahashi et al, 2019;Tine, 2014;Tine & Butler, 2012;Tsai et al, 2014Tsai et al, , 2016Tsorbatzoudis et al, 1998;Tsukamoto et al, 2017;Van den Berg et al, 2018;Vonk et al, 2019;Wang et al, 201...…”
Section: Resultsmentioning
confidence: 99%
“…The role of exhaustion remains as a topic for future investigations. Furthermore, mechanisms explain our results may include but not be limited to arousal levels [27], higher activity of neurotransmitters related to attention [28], and increases in the release of catecholamine resulting in increased activation of the prefrontal cortex, which facilitate perception and attention performance [29].…”
Section: Discussionmentioning
confidence: 95%